A unique choline nitrate-based organo-aqueous electrolyte enables carbon/carbon supercapacitor operation in a wide temperature window (−40°C to 60°C) - Supiyeva, Zhazira; Mansurov, Zulkhair; Azat, Seitkhan; Abbas, Qamar (Frontiers in Chemistry, 2024)
Some drawbacks of aqueous electrolytes, such as freezing at low temperatures and extensive evaporation at high temperatures, restrict their industrial viability. This article introduces a stabilized neutral aqueous choline nitrate electrolyte with a 10 vol.% methanol additive that improves the temperature stability of the electrolyte via enhanced hydrogen bonding with the choline cation and water and maintains the good state of health of the supercapacitor cells under extreme operating conditions. The symmetric carbon/carbon supercapacitor in 5 mol/kg choline nitrate + 10 vol.% methanol (σ = 76 ms/cm at 25°C) exhibits 103 F/g at room temperature during galvanostatic charge/discharge up to 1.5 V, which decreases to 78 F/g at −40°C due to the suppressed Faradaic reactions occurring at the carbon electrode. However, under similar charge/discharge conditions, the capacitance increases to 112 F/g when the supercapacitor operates at 60°C. This capacitance increase at high temperatures is due to the Faradaic reactions related to enhanced hydrogen adsorption and desorption. The most remarkable aspect of the proposed supercapacitor is its ability to maintain capacitance and power performance during high voltage floating at 1.5 V at three tested temperatures (−40°C, 24°C, and 60°C).